Analysis of poultry market chain: The case of Dale and Alaba ‘Special’ Woredas of SNNPRS, Ethiopia - Zeberga, A. (Haramaya University, 2010)
The purpose of this study was to analyze the poultry marketing chain in Dale and Alaba ‘special’ weredas of SNNPRS, Ethiopia. The specific objectives include analysis of the structure, conduct and performance of poultry marketing system, production and marketing support services of extension, input supply, credit and marketing. Cost structure and profitability of village poultry keeping were also analyzed. Furthermore, factors that affect farmers’ decision to participate in the supply of live birds and egg to the market and volume of birds and egg supplied to the market were identified in the study. Constraints and opportunities of production and marketing of poultry in the study area were also assessed. To address the aforementioned objectives descriptive statistics and econometric models were employed. Moreover, various marketing agents and their roles, linkages and functions in the poultry marketing system were also assessed. Alternative marketing channels and their systematic linkages and relative importance in the flow of birds and egg from the point of production to the end users were identified and mapped. Heckmans’ two stage and Tobit econometric models were employed to identify factors that determine the farmers’ participation decision and the amount of birds and egg supplied to the market in the year 2007/8 E.C. Village collectors, urban assemblers and whole sellers played crucial roles in the sample markets in the transaction of birds and egg from producers to consumers. Strong oligopolistic behavior is observed in Yirgalem and Alaba egg markets wit 98 and 93 percent concentration ratio respectively due to the short and inconsistent supply of egg that inhibits new entrants to engage in the business. Live bird trading in Alaba market also shows modest oligopolistic behavior (59.7% concentration ratio) due to the involvement of whole sellers who transport their birds to Addis Ababa market that comparatively demands high capital and information than the Awassa and Yirgalem poultry market places. Business support services such as credit, extension, input provision and information access in the production and marketing of village poultry are poorly developed or almost nonexistent in the study area. xvii According to the study the production and trading of live birds and egg are profitable in smallholders’ production system due to its’ low and abundant input requirements such as capital and labor than alternative business activities. From the probit model factors that determine the farmers’ participation decision are identified. These includes sex of the house holdhead, family size, total number of birds kept and feed supplementation have highly significantly influences farmers’ decision to supply chickens and eggs to the market. According to the result of the linear supply function and Tobit models, the total number of birds that the family kept, feed supplementation, market access, purpose of poultry keeping, producers participation decision in bird and egg supply and Credit use are found to have highly significant impact on the value of volume of birds and egg supplied to the market. The village poultry subsector provides ample opportunities for smallholder farmers since it utilizes resources that are abundant in rural areas and the anticipated rising price and demand in domestic and international markets. The subsector was also constrained by various challenges. According to the market survey, traders face lack of capital, short and inconsistent supply and, poor information and infrastructure development such as storage, packaging and transportation facilities. The production of village poultry was also constrained by diseases (NCD), predation, lack of input and volatile price and demand. Despite the numerous challenges the subsector still remains profitable business for the rural poor.